Manajemen Pendidikan dalam Perspektif Islam - Muhammad Madarik (LPPI Universitas Al-Qolam Malang, 2025)
The basic principles of management can be narrowed down to four things: [1] people; [2] resources; [3] goals; and [4] time. When these four elements are realized, they appear as a social unit called an